2008
DOI: 10.1093/europace/eun028
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte concentration during haemodialysis and QT interval prolongation in uraemic patients

Abstract: Changes in ventricular repolarization duration associated with HD largely depend on the concentrations of Ca(2+) and K(+) in the dialysis bath. These findings may have important implications for the choice of the electrolytes concentration of the dialysis bath during the HD session.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 31 publications
(36 reference statements)
5
101
0
2
Order By: Relevance
“…21 Genovesi et al, 22 utilizando dialisatos com diferentes concentrações de cálcio (K + de 2 e 3 mmol/L; Ca 2+ de 1,25 ou 1,5 ou 1,75 mmol/L), observaram QTc > 440 ms em 56% dos pacientes cujo dialisato continha as mais baixas concentrações de cálcio e de potássio e em apenas 18% dos pacientes em que foi prescrito dialisato com as concentrações mais elevadas desses íons. Resultados semelhantes foram encontrados por Di Iorio et al, 23 em que o intervalo QTc foi mais prolongado de modo significativo em pacientes cujo dialisato continha as mais baixas concentrações de cálcio e potássio e as mais altas concentrações de bicarbonato.…”
Section: Discussionunclassified
“…21 Genovesi et al, 22 utilizando dialisatos com diferentes concentrações de cálcio (K + de 2 e 3 mmol/L; Ca 2+ de 1,25 ou 1,5 ou 1,75 mmol/L), observaram QTc > 440 ms em 56% dos pacientes cujo dialisato continha as mais baixas concentrações de cálcio e de potássio e em apenas 18% dos pacientes em que foi prescrito dialisato com as concentrações mais elevadas desses íons. Resultados semelhantes foram encontrados por Di Iorio et al, 23 em que o intervalo QTc foi mais prolongado de modo significativo em pacientes cujo dialisato continha as mais baixas concentrações de cálcio e potássio e as mais altas concentrações de bicarbonato.…”
Section: Discussionunclassified
“…Haemodialysis per se is a risk factor for arrhythmias due to rapid the electrolyte shifts and cardiovascular instability (intradialytic hypotension) that can occur with this treatment (10)(11)(12)(13). Rapid potassium and calcium shifts during HD sessions and low levels of electrolytes in the dialysate increase the risk for cardiac arrhythmia (10)(11)(12)(13).…”
Section: Rapid Electrolyte Shiftmentioning
confidence: 99%
“…Rapid potassium and calcium shifts during HD sessions and low levels of electrolytes in the dialysate increase the risk for cardiac arrhythmia (10)(11)(12)(13). The use of potassium-free or low-potassium dialysates (K + d = 1.0 mmol/L), particularly at the beginning of a dialysis session, removes potassium quickly, causing a rapid decline in the patient's serum potassium concentration, which may lead to a disturbance of ventricular myocardial repolarisation, an increase in the corrected QTc interval (QTd) dispersion and increased risk for ventricular arrhythmias (10)(11)(12)(13).…”
Section: Rapid Electrolyte Shiftmentioning
confidence: 99%
“…Acute alcoholic states, binge drinking, the "holiday heart syndrome" and liver cirrhosis are associated with prolonged QT intervals and an increased prevalence of cardiac arrhythmias and SCD (Day et al, 1993;Genovesi et al, 2008;Wever & Robles de Medina, 2004;). In contrast, case-control studies have demonstrated a protective effect of moderate alcohol consumption against sudden cardiac death (Priori et al, 2001;Vreede-Swagemakers et al, 1999).…”
Section: Alcoholismmentioning
confidence: 99%